A spatial analytical hierarchy for Gap Analysis - Davis, F. W.; Stoms, D. M. (Gap Analysis: A Landscape Approach to Biodiversity Planning, 1996)
Representation in the nature reserve system is determined by comparing the distribution of vegetation and vertebrates with that of land ownership and management over a region of interest. Locating potential places to increase representation is typically done by a systematic selection algorithm over a set of spatial units larger than the landscape units of the vegetation map. The landscape is thus the basic spatial unit at which biodiversity data are compiled for Gap Analysis. However, it is only one of four levels of spatial entity that must be explicitly defined in order to complete a Gap Analysis. We refer to these entities as the planning region, the planning unit, the landscape, and the landscape feature. The objective of this paper is to describe a spatial analytical hierarchy for Gap Analysis based on these four entities. Within this broader theme we also present results of a more focused analysis on the effect of planning unit size on the selection of priority conservation areas in southwestern California.
Keywords: gap analysis; reserve selection; scale